MENATA ULANG LAYOUT FASILITAS PERPUSTAKAAN UNIVERSITAS KRISTEN PETRA SESUAI KEBUTUHAN GENERASI DIGITAL NATIVE - Felecia, Felecia; Wulandari, Dian; Halim, Siana (Association of Indonesian Library and Information Professionals, 2018)
One aspect of library quality is as ?library as a place?. As the main aspect that influences customer satisfaction, the library as a place needs to get attention from the library including structuring the layout of library facilities. This study aims to determine the layout of library facilities according to the needs of the native digital generation at the Christian Petra University Library. If library facilities are arranged with a good layout, there will be an increase in productivity, work efficiency and will have an impact on customer satisfaction. The Head of the Library and/or structural officials were chosen as respondents because they were more aware of the relationship between the sections and understood the needs of the generation of digital natives currently served. The method used in this study is systematic layout planning by adopting the ARC (Activity Relationship Chart) technique to show the level of importance between departments/sections, and the results will be used as a replacement of flows between departments/sections. CRAFT is used as a computer simulation tool to improve facility layout (re-layout) by minimizing the moment of movement between facilities. The results showed that it was necessary to rearrange Petra?s UK library facilities on each floor, in which the results of this study was surely tested through a questionnaire for students who were digital native generation and were the largest users of the library.